Development of the Idea of the Integration of the Blind in Lithuania - Andrejauskas, Vladas (Problemos, 1980)
The idea of the integration of the blind envisages certain changes in their social life mainly because this idea embraces a consideration concerning social foundations of education, vocational training and employment of the blind. The promulgation of this idea in Lithuania in the nineteenth century took place under the influence of the activity of wardship organizations for the blind in Tsarist Russia. The present paper focusses on the evaluation of the realization of social programs for the integration of the blind in bourgeois Lithuania.